Investigating the performance of thermal spray coatings on agriculture equipment - Linde, George Frederick (Stellenbosch : Stellenbosch University, 2016)
ENGLISH ABSTRACT: In the agricultural industry there are different wear problems that need to be managed in order to extend the operating life of equipment. The agricultural industry is a great asset to all South Africans in terms of food production and employment. Purchasing and maintaining agricultural machines and equipment are major cost items for agri businesses. There are many problem areas in this industry and the people carrying the consequences include farm equipment manufacturers, farm contractors, farmers and organisations that process the harvested crops in agro-processing. Equipment used in various applications is subject to different kinds of wear caused by different materials in different operating conditions. The focus of this research is limiting wear, mainly caused by grain (maize and wheat), during agro-processing and transformation in storages, such as silos. Wear problems occur in mills and silos where grain is stored in large quantities and moved through the process of agroprocessing. There are different ways and methods of limiting wear and increasing the performance of the equipment used in the agricultural industry. Different thermal spray coatings were tested to evaluate their ability to limit the wear that may causes a decrease in the performance of the equipment in agro-processing. Different coatings of tungsten carbides and chrome oxides and carbides were sprayed onto five specimens using different thermal coating processes. The behaviour of these different coatings was tested by objecting them to constant wear. The constant wear was applied using silicon carbide grinding stone that was mounted to a Dremel tool. The Dremel tool was mounted to a CNC machine to control the grinding parameters. The experiment tested the coatings under constant conditions before they were installed into a silo, to test the coatings in a real world application. The objective of the research was to find the balance between the cost and performance of the different coatings.